Legal Status of Execution of Liability Auction Winner through Parate Executie - Hetharie, Yosia (Damhil Law Journal, 2023)
This study aims to analyses the execution of mortgage rights, namely executorial title, parate executie, and underhand execution. Parate executie is carried out by the holder of the first mortgage right if the debtor defaults through the State Property and Auction Service Office. The provisions and procedures for conducting an auction are regulated in the Regulation of the Minister of Finance Number 213/PMK.06/2020 Concerning Instructions for Conducting Auctions. However, in practice there are still many problems or conflicts and many obstacles that occur. For example, there is no legal certainty for auction winners who have good intentions because they cannot immediately obtain their rights legally and materially. The type of research used in this study is normative juridical research which is descriptive analytical using a qualitative approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials through library research. Based on the research results, the Auction Winner as a buyer in good faith has a position as the right holder of the auction object both formally and physically as a mortgage object. Therefore, the winner of the auction with good faith is entitled to all of his rights both in terms of formal juridical evidence and the physical object of the mortgage object. In this position, theÂ State Wealth and Auction Service Office has the responsibility of examining all sales conditions and fulfilling all stages and appointing an auction official as the executor of the sale so that as long as the requirements and processes are carried out according to the instructions for conducting the auction.